Analysis of the Implementation of Patient Safety Culture with the AHRQ Model at Mitra Medika Hospital Tanjung Mulia Medan - Naeni Juliani; Arifah Devi Fitriani; Deli Theo (Newinera Publisher, 2021)
Safety Culture is a collaborative environment where clinical staff treat one another with respect by involving or empowering patients and families so that each Professional provides patient-focused care. The purpose of this study was to determine the implementation of a patient safety culture with the AHRQ model in Mitra Medika Tanjung Mulia General Hospital Medan. This research uses a mix of methods, namely qualitative and quantitative. The population of this study were all staff on duty in each hospital unit associated with 450 patients at MItra Medika Hospital, so the sample was 75 people using simple random sampling technique. The main research informants were one officer each in each installation.Unit Mitra Medika Tanjung Mulia General Hospital Medan, namely 10 people, one key informant, and one triangulation informant.The results of the study show that the description of expectations and managerial actions of patient safety is 68%, organizational learning is 100%, cooperation in units is 76%, communication open by 80%, feedback about the error of 75%, the dimension of non-punitive response to errors is 55%,Staffing 51%, management support for patient safety efforts by 77%, cooperation between units of 61%, handsoff work and changing patients was 71%,the overall perception of hospital staff about patient safety was 63%, reporting frequency was 63%. With the research results, it is expected that Mitra Media Tanjung Mulia General Hospital Medan is expected to be able to initiate, maintain, and develop an ongoing patient safety program and implement the existing safety culture.